Rejtőzködő városi menekültek Bangkokban - Dániel, Solymári; Bence, Tamássy (Acta Humana, 2021)
According to the Thai Immigration Act, refugees arriving to the country are illegal immigrants. The main reason for this is that the Kingdom has not yet ratified the 1951 Refugee Convention, thus it does not accept refugee applications, it does not recognise this status. The police can detain illegal residents and can initiate criminal proceedings against them. However, this vital topic of international dialogue is less known in Hungary. In our work, we review the local and international legal framework affecting the reality of the Thai refugee crisis, and point out the humanitarian crisis that has arisen through the enforcement of Thai law. Our paper is focused on the issue of legal protection that people who qualify as refugees under the Geneva Convention on Refugees can expect in a country that has not ratified the Convention and does not have an asylum system.